National Program for Independent Rural Community Empowerment (PNPM-MP) in Realizing Welfare in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency - Rizal Fahlevi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
Community empowerment is an effort to increase the dignity of the community layer out of the trap of poverty and underdevelopment so that the government programs assistance intended for the poor, one of which is the National Program for Independent Rural Community Empowerment (PNPM-MP). The research method used in this study is a qualitative descriptive method. The results of this study indicate that the implementation of the National Program for Independent Rural Community Empowerment (PNPM-MP) in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency has been carried out well, especially with regard to the implementation of infrastructure development.